Control Strategies of a Gas Turbine Generator: A Comparative Study - Lyes Abbassen; Mustapha Zaouia; Nacereddine Benamrouche; Amar Bousbaine (IAES Indonesian Section, 2020)
Gas turbine generators are commonly used in oil and gas industries due to their robustness and association with other operating systems in the combined cycles. The electrical generators may become unstable under severe load fluctuations. For these raisons, maintaining the stability is paramount to ensure continuous functioninality.This paper deals with the modeling and simulation of a single shaft gas turbine generator using the model developed by Rowen and incorporating different types of controllers, viz a Zeigler- Nichols PID controller, a Fuzzy Logic Controller (FLC), FLC-PID and finally a hybridPID/FLC/FLC-PIDcontroller. The study was undertaken under Matlab / Simulink environment with data related to an in service power plant owned by Sonatrach, Algiers, Algeria. The results show that FLC-PID and hybrid tuned controllers provide the best time domain performances.